“Eu te falei de Mariana, do rompimento da barragem?”: sussurros da educação ambiental entre profissionais da educação básica pública, Nepomuceno, Minas - Liberato, Vanderléia das Dores Silva (2017)
Over the years the numerous transformations in society have brought a lot of evolution and benefits, and, on the other hand, many social risks. Among the risks and problems emerging each day, they deserve to highlight environmental problems, being discussed in various research camps. With the increase in environmental problems, it is important that society in general reflect, rethink actions and practices, often naturalized and reproduced everyday, proposing new proposals and alternatives that contribute to minimizing environmental problems. In the context of these alternatives, we visualize the union of several areas of knowledge as attempts to combat the effects of human action on the planet. In this sense, the area of Education, through Environmental Education has gained prominence in seeking greater reflection and participation of the subjects in the face of these problems. Since the environmental problems began to be perceived by society, several movements and social groups began to emerge, claiming a position of the different social actors. From various groups and social movements, of international and national meetings, it becomes increasingly formalized the environmental education, being in Brazil established by Law n° 9.795, of 27 April 1999 – National Policy of Environmental Education. From this policy, Environmental Education was inserted in a transversal and interdisciplinary form in the formal and non-formal education spaces. In the face of this, we must think about how the work of environmental education is happening in the school spaces. Thus, we seek this research to investigate the conceptions of Environmental Education of professionals of the basic public education of Nepomuceno, MG, as well as verifying the approach of the theme, knowing the didactic strategies that are being used for this work, and those that are necessary, in the background of the work of schools in relation to local socio-environmental reality. The type of research was the Case Study in the qualitative approach, with field research. For the collection of data we use a roadmap for a very structured interview and a closed questionnaire for an individual interview. The analysis of the results has been achieved through the thematic content analysis technique. From the results, we find that in reality investigated, the practice of EE happens in a punctual way limited to commemorative dates, except for some cases coming through the occult curriculum. The research data showed that EE is not part of the Pedagogical Political Project (PPP), demonstrating a lack of knowledge of this collective and democratic tool in the school field. From the theoretical study pertinent to the thematic in question, as well as all analyses of the results of the survey, it is valid to highlight that, despite the fact and happens in a punctual manner, presenting ignorance of the theme through a formal education process by the professionals in the municipality, even so, many people already do EE in the everyday educational practices. Faced with this fact, we consider that these practices can be a seed to germinate in the future, based on a perspective of EE criticism.